Entrepreneurship and an aging population - Mikaela Backman; Charlie Karlsson (European Regional Science Association (ERSA), 2013)
There is a tendency in Europe that older individuals are those most prone to start a new firm. This paper analyses if this statement is true also for Sweden. A first approach is to analyze the tendency at the regional level where the influnce from different age cohorts on the rate of new firm formation is analysed. In the second stage, an individual perspective is taken where the probability to start a new firm is expected to increase as individuals become older. By decomposing the population in different age cohorts it is possible to find differences in the probability of start new firms, is it so that individuals over the age of 55 have a higher probability to start a new firm. A third stage handles the survival rate of the firms started by elder individuals. Thus, it is possible to investigates whether the firms started by elder individuals is more likely to survive. To increase and deepen the knowledge about the relationship between age and entrepreneurship this paper adds to existing literature by separating regions into different categories along a urban-rural hierarchy.
Keywords: 330; new firm formation; age cohorts; urban-rural hierarchy; Sweden